How Work Motivation Shapes the Effects of Leadership, Compensation, and Job Satisfaction on Employee Performance: Evidence from Timor-Leste - Veronica Sunarto Ximenes; Miswanto Miswanto; Titik Kusmantini (MultiTech Publisher, 2026)
Employee performance is widely recognized as a key determinant of organizational effectiveness, yet empirical evidence on the roles of leadership style, compensation, job satisfaction, and work motivation remains inconclusive. This study examines the effects of leadership style, compensation, and job satisfaction on employee performance and evaluates the moderating role of work motivation. A quantitative explanatory design was employed using survey data collected from 200 employees of organizations in Timor-Leste through purposive sampling. The hypotheses were tested using Moderated Regression Analysis (MRA). The results show that leadership style and compensation have positive and significant effects on employee performance, whereas job satisfaction does not significantly influence performance. Work motivation strengthens the positive effects of leadership style and compensation, indicating that motivated employees benefit more from effective leadership and equitable compensation. By contrast, work motivation weakens the relationship between job satisfaction and employee performance, suggesting that highly motivated employees rely less on job satisfaction to sustain their performance. These findings extend Social Exchange Theory by showing that the role of work motivation depends on the organizational context and the antecedents of employee performance.